Major determinants of interest rate movements in Singapore - Chua, Chai Hoon (2015)
Since the interest rate liberalisations initiated by the Monetary Authority of Singapore in 1975, there has been significant fluctuations in the domestic interest rates. Among the different interest rates, the three-month interbank rate is closely monitored by various bodies such as the Singapore Government, financial institutions and corporations. This is because the rate is frequently used as a benchmark £or setting other rates, thus playing an important role in determining the level of activity in the economy. It is therefore the aim of this report to identify the major determinants of the three-month interbank rate. A literature survey was first conducted on the theoretical approaches to interest rate determination. This was followed by studies presented by various academics to determine the domestic interest rates. An econometric model was subsequently developed and tested using MicroTsp programme. Our estimation results show that domestic interest rate was susceptible to changes in both domestic and foreign economic developments, although the extent of foreign influence on interbank rate is small as compared to the impact exerted by domestic variables. This may be explained by the fact that the Monetary Authority of Singapore (MAS) intervenes actively in the foreign exchange market. Subsequently, bank liquidity, which represents domestic influences, exerted the most significant impact on interest rates. Besides the quantifiable variables, our model attempted to capture the 'qualitative' effects of the various major events which have significant impact on the three-month interbank rate. These dummy variables were found to be statistically significant in the determination of the interbank rate. In conclusion, local factors seemed to have a greater impact on the three-month interbank rate as compared to foreign influences. As such, participants in the interbank market should monitor the domestic developments closely but bearing in mind that events overseas may have an impact on the domestic economy.